the Effect of Knowledge, Motivation, Organizational Culture on Medical Record Compliance Compliance in Hospitals - Suriviana Suriviana; Rokiah Kusumapradja; Lily Widjaya (Jurnal Health Sains, 2023)
Every health service facility is required to make medical records made by doctors and health workers related to the services that have been provided. The completeness of the information provided by health workers shows that the quality of the health services provided can be proven to be following related health service standards. This study was to analyze the influence of knowledge, motivation, and organizational culture simultaneously on compliance with medical record filling at Mitra Medika Hospital Pontianak using 83 respondents using the mixed methods sequential explanatory designs. From the results of the quantitative research, it was found that the Knowledge and Organizational Culture variables influenced compliance with medical record filling with beta values ​​of 0.567 and 0.416; as well as the significance of both variables 0.000; Meanwhile, motivation does not affect compliance with medical record filling with a beta value of 0.003 and a significance of 0.940; Knowledge is the variable that has the most dominant influence on compliance with medical record filling. From the results of qualitative research, it was found that motivation does not affect the value of the dimensions of motivation. Where knowledge and organizational culture influence the filling of medical records by the values ​​of the dimensions of knowledge and organizational culture.